ELIPSIS DALAM KITAB INJIL YOHANES BERBAHASA INGGRIS (Suatu Analisis Sintaksis) - POYUNGI, YURIKE SUHERTIAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This research entitled â€œEllipsis in the Book of Johnâ€ is written to identify, classify and analyze the kinds of ellipsis that found in the book of John. Ellipsis is the omitting of certain lingual units which have mentioned previously and the omitting elements are words, phrases, clauses or sentence. The method used in this research is descriptive method. The data were taken from the book of John based on The Holy Bible New International Version. The writer uses aÂ theory of Aarts and Aarts (1982) to classify and analyze the kinds of ellipsis. The kinds of ellipsis found in the book of John are : ellipsis involving the subject only, ellipsis involving the subject and (part(s) of) the predicator, ellipsis involving, (part(s) of) the predicator, ellipsis involving (part(s) of) the predicator and a complement or adverbial and ellipsis involving a complement or an adverbial only. The writer also found the others kinds of ellipsis which is not included in the theory of Aarts and Aarts, they are : ellipsis involving the subject, predicator and complement, ellipsis involving the subject, adverb and predicator, ellipsis involving the subject that followed by adjective clause. Key words: syntax, ellipsis. The Book of John